Experimental Ixodes ricinus-Sheep Cycle of Anaplasma phagocytophilum NV2Os Propagated in Tick Cell Cultures - Almazán, Consuelo; Fourniol, Lisa; Rouxel, Clotilde; Alberdi, Pilar; Gandoin, Christelle; Lagrée, Anne-Claire; Boulouis, Henri-Jean; de la Fuente, José; Bonnet, Sarah I. (Frontiers in Veterinary Science, 2020)
Anaplasma phagocytophilum, the causative agent of human anaplasmosis and tick-borne fever in sheep, is transmitted by Ixodes ricinus throughout Europe, and is currently considered as an emerging disease. In this study, we describe the establishment of a model of A. phagocytophilum sheep infection and I. ricinus transmission by using the European most well-known Norway variant 2 ovine strain (NV2Os) propagated in IDE8 tick cells. Two sheep were inoculated with tick cells infected with the A. phagocytophilum NV2Os. Four days post inoculation (dpi), both sheep developed A. phagocytophilum infection as determined by PCR and the presence of fever, morulae observation in granulocytes at 6 dpi, and Anaplasma antibodies detection at 14 dpi. Necropsies performed at 14 and 15 dpi allowed to detect A. phagocytophilum by immunohistochemistry in skin sections as well as by PCR in skin, lung, small intestine, liver, spleen, uterus, and mesenteric lymph nodes. At 6 dpi, during the acute phase of infection, one sheep was infested with larvae, nymphs and adults of I. ricinus from a pathogen-free colony. After molting, A. phagocytophilum transstadial transmission in ticks was validated in 81% of nymphs and 80 and 90% of salivary glands and guts from adult females, respectively. As expected, no transovarial transmission was found. We then demonstrated that the infected nymphs were able to transmit the bacteria to one of two other naive infested sheep. Finally, sheep infected blood collected at 14 dpi was demonstrated to be able to infect ISE6 tick cells allowing the infection of two additional naive sheep that developed similar clinical signs than the previous infected ones. One of the animals died and the other remained persistently infected until 115 dpi when it was euthanized. This sheep transmitted the bacteria to 2.7% nymphs engorged as larvae during persistent infection. The establishment of this experimental model allows addressing research questions on a tick-borne bacterium of increasing importance.